The Iron Age complex of the Mastara mountain valley in the system of cultural landscape of Karmrashen Saravand - Mkrtchyan, Levon (History and Culture, 2025)
The article is dedicated to the Mastara mountain valley, one of the zones forming the cultural landscape of the Karmrashen peninsula, where we have confirmed a number of newly discovered (left out of scientific circulation) monuments, which, according to preliminary observation, form a single complex.The Karmrashen Peninsula extends in the southwestern parts of the Aragatsotn Marz of the Republic of Armenia and the western parts of the Armavir Marz, at the southwestern foot of the Aragats massive, between the Talin Peninsula and the Akhuryan and Araks rivers. It is rich enough in historical and cultural monuments, because it was included from different sides and was part of Shirak and Aragatsotn provinces on the one hand, bearing the influences of their cultural developments, from the Bronze-Iron Age to the Middle Ages. Based on the above, this zone has always been in the center of attention of researchers. Archaeological expeditions of different years of the Archaeological Research Laboratory of Yerevan State University have a particularly great contribution to the study of the cultural landscape of this peninsula (study: P. Avetisyan, E. Asatryan, H. Ohanyan and others).Perhaps we are dealing with a center of local significance typical of the Iron Age (9-6th centuries BC), which, together with other similar neighboring examples (Lanjik, Tsakasar, Akunk 1, etc.) formed larger units, which are known from the Bianic inscriptions are under the name Etuinian «countries».
Keywords: Karmrashen Saravand; cultural landscape; bronze-iron centuries; fortress; tower